A taxonomic revision of South American species of the seed-harvester ant genus Pogonomyrmex (Hymenoptera: Formicidae). Part I - Johnson, Robert A. (Zootaxa, 2015)
South American species in the seed-harvester ant genus Pogonomyrmex (subfamily Myrmicinae) are interesting biologically because of their numerous queen phenotypes and life histories. This paper provides a taxonomic revision and reviews the natural history for 21 South American species of Pogonomyrmex so that we can better study their rich and interesting ecology, life history, and evolution. Species treated herein comprise all South American species-groups except for the brevibarbis and rastratus-groups. The following taxa are raised to species: pencosensis Forel 1914 and serpens Santschi 1922. The following new synonomies are proposed: bruchi Forel 1913 is synonomized under coarctatus Mayr 1868 and cunicularius carnivora Santschi 1925 under serpens Santschi 1922. The following new species is described: tinogasta. This paper redescribes workers of all species, and I describe queens and diagnose males for the following species: bispinosus (ergatoid queen, male), inermis (queen, male), laticeps (male), lobatus (queen, male), micans (queen), naegelii (ergatoid queen), pencosensis (ergatoid queen), serpens (ergatoid queen), tinogasta (brachypterous queen), and uruguayensis (queen, male). A neotype was designated for the untraceable or possibly lost type of P. bispinosus, and a holotype or lectotype was designated from syntypes for all other previously described taxa in order to provide a single name-bearing specimen and to facilitate future taxonomic studies. Of the 21 species treated herein, five species have ergatoid (wingless) queens (bispinosus, cunicularius, pencosensis, serpens, mayri), two have brachypterous (short-winged) queens (mendozanus, tinogasta), and two have dimorphic queens (winged and ergatoid in naegelii, brachypterous and ergatoid in laticeps). I also provide keys for workers and queens (in English and Spanish), photographs of all castes, distribution maps, and a summary of known biology.